Observation of superfluidity in two- and one-dimensions - Wada, Nobuo; Hieda, Mitsunori; Toda, Ryo; Matsushita, Taku (Физика низких температур, 2013)
Even though there is no long-range-ordered state of a superfluid in dimensions lower than the three-dimension (3D) such as bulk ⁴He liquid, superfluidity has been observed for flat ⁴He films in 2D and recently for nanotubes of ⁴He in 1D by the torsional oscillator method. In the 2D state, in addition to the superfluid below the 2D Kosterlitz–Thouless transition temperature TKT, superfluidity is also observed in a normal fluid state above TKT, which depends strongly on the measurement frequency and the system size. In the 1D state of the nano-tubes, superfluidity is directly observed as a frequency shift in the torsional oscillator experiment. Some calcula-tions suggest a superfluidity of a 1D Bose fluid with a finite length, where thermal excitations of 2-phase winding play the main role for superfluid onset of each tube. Dynamics of the 1D superfluidity is also suggested by observing the dissipation in the torsional oscillator experiment.